Selected chemical and physical properties of soils planted with vegetables at Kundasang Sabah - Kasim, Susilawati; Rosidi, Nur Adila; Mohd Shuib, Effyanti; Ahmed, Osumanu Haruna; Ahmad, Khairulmazmi; Ismail, Mohd Razi; Abd. Rahman, Nordin (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Soil chemical and physical properties relate to soil quality or health. This paper reports preliminary evaluation of soils planted with vegetables at Kundasang, Sabah. The plots were categorized based on texture. Systematic sampling was used to sample soil (0 to 20 and 20 to 40 cm) in the plots after which the samples were analysed using standard procedures. Total N in three plots was different and the difference range from 0.06 to 0.1%. The ranged suggest high N requirement. Minimum addition of N fertilizer in the area could be the reason for this finding. This implies that application of chicken manure may not be helpful in optimizing N content in the soil. Upper soil part (0 to 20 cm soil depth) recorded higher total carbon and organic matter content in the study plots. This is normal for mineral soils where most of organic matter get accumulated in the upper part of the soil. Total P in all of the sampled plots were generally high (>50 ppm using Mehlich 3 method). Sandy clay loam soil at 0 to 20 cm (1674.83mgkg-1) and 20 to 40 cm (to 6276.39 mgkg-1) showed higher P. Slope and texture could be attributed to this finding. In conclusion, the chemical and physical properties of soils were different in all the three plots and generally higher values were observed for upper part of the soils. A detail study in the area is recommended so as to identify the effects of the chemical and physical properties on the yield of vegetables. The relationship between the variables evaluated with management practices need to be further studied to verify the findings reported in this paper.